2020
DOI: 10.12688/hrbopenres.13025.2
|View full text |Cite
|
Sign up to set email alerts
|

Steps Ahead: optimising physical activity in adults with cystic fibrosis: Study Protocol for a pilot randomised trial using wearable technology

Abstract: Background: Physical activity (PA) and exercise are widely documented as key components in the management of cystic fibrosis (CF). In recent years there have been significant improvements in telehealth, in particular; wearable technology,  smartphone use and remote monitoring, all of which may have potential to impact on PA in adults  with CF. The objective of this pilot randomised trial is to explore the effect of wearable technology, which is remotely monitored, combined with personalised text message feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…However, further prospective research that we are currently conducting will provide clarity on the nature of these relationships. 49 In a systematic review and meta-analysis in PWCF, Shelley et al 16 also found that participants did not achieve recommended PA guidelines or step count targets in most studies. We also found that females were 25% less active than males, which is corroborated by previous research in a CF population.…”
Section: Discussionmentioning
confidence: 99%
“…However, further prospective research that we are currently conducting will provide clarity on the nature of these relationships. 49 In a systematic review and meta-analysis in PWCF, Shelley et al 16 also found that participants did not achieve recommended PA guidelines or step count targets in most studies. We also found that females were 25% less active than males, which is corroborated by previous research in a CF population.…”
Section: Discussionmentioning
confidence: 99%